The disappearing limb trick and the role of sensory suggestibility in illusion experience. (August 2018) - Stone, Kayla D.; Bullock, Femke; Keizer, Anouk; Dijkerman, H. Chris
Abstract: Body ownership (the feeling that my body belongs to me) can be easily perturbed in healthy individuals by inducing bodily illusions. For example, dis-integrating vision, touch, and proprioception can produce the feeling that your limb is 'lost', such as in "the disappearing hand trick" (DHT). Following this illusion, participants report that the hand feels as though it is no longer part of the body, that it does not belong to them anymore, and that they do not know its location. However, it remains unknown whether this illusion can also be applied to the feet. Lower body ownership is disturbed in some populations, such as in Body Integrity Identity Disorder (BIID), where people have a longstanding desire to paralyze or amputate a (disowned) part of their body (i.e. usually the legs), thus exploring the efficacy and utility of lower body illusions might be useful for populations like such. In the current study, we induced the disappearing hand and foot trick in two groups of healthy adults. As the illusion crucially relies on illusory sensory feedback, we also explored if one's level of sensory suggestibility influenced the experience of the illusion. Questionnaire data showed that the DHT can be applied to the feet, as there was no difference in experience between those who experienced the illusion for the hands and those who experienced the illusion for the feet. Moreover, one's level of sensory suggestibility correlated positively with the experience of illusory sensations (like warmth, numbness, or the presence of an extra limb) following the illusion. We discuss the implications of bodily illusions in clinical populations and emphasize the critical role that sensory signals (even illusory) play in creating the bodily experience. Highlights: Subjective experience of a body illusion was compared between the hands and feet. The subjective experience of the illusion for the hands and feet did not differ. The relation between illusion experience and sensory suggestibility was measured. Illusory sensations during the body illusion correlated with sensory suggestibility. Multisensory processes for upper body illusions likely generalize to the lower body.